2020
DOI: 10.3390/ijerph18010130
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Eating in Relation to Worries and Psychological Distress Amid the COVID-19 Pandemic: A Population-Based Survey on Adults in Norway

Abstract: Population-based studies have revealed a high occurrence of self-reported psychological distress symptoms during the early phases of the coronavirus disease 2019 (COVID-19) pandemic. Stress and negative affect can lead to emotional eating, which in turn can have negative outcomes on health. In this population-based study, 24,968 Norwegian inhabitants participated in an electronic questionnaire including structured questions on dietary habits, emotional eating, psychological distress symptoms, and COVID-19-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
6
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 35 publications
8
78
6
5
Order By: Relevance
“…Considering diagnostic subpopulations, admissions for biliary tract pathology were similar if not slightly higher in 2020 relative to 2019. This observation appears consistent with what is known about dietary and other lifestyle changes that occur(ed) during the pandemic that are known to exacerbate biliary tract disease [17][18][19]. It may be the case that there was some decline in "appendicitis" cases based on fewer presentations of right lower quadrant pain that…”
Section: Plos Onesupporting
confidence: 85%
“…Considering diagnostic subpopulations, admissions for biliary tract pathology were similar if not slightly higher in 2020 relative to 2019. This observation appears consistent with what is known about dietary and other lifestyle changes that occur(ed) during the pandemic that are known to exacerbate biliary tract disease [17][18][19]. It may be the case that there was some decline in "appendicitis" cases based on fewer presentations of right lower quadrant pain that…”
Section: Plos Onesupporting
confidence: 85%
“…A study from Denmark also observed a higher degree of emotional eating during the lockdown, e.g., increased consumption of pastries and alcohol (11). In Norway, it was found that consumption of high sugar food and beverages was greater for those with increased COVID-19 related worries and general psychological distress than the overall population (12).…”
Section: Introductionmentioning
confidence: 94%
“…Intolerance of uncertainty can result in anxiety [ 19 ], and can lead to maladaptive or adaptive strategies to cope with it [ 20 ]. While maladaptive strategies may cause more distress—and, sometimes, an increase in eating disorders [ 20 , 21 , 22 ]—adaptive strategies help to reduce anxiety levels and increase self-esteem [ 23 ]. The identification of such resources and their incorporation into health strategies is essential to help individuals deal with the loss of control and uncertainty and to support their acceptance and stabilization [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%